2023
DOI: 10.1007/s00403-023-02574-w
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser in the treatment of nail psoriasis: how can it help?

Abstract: Treating nail psoriasis is often a time-consuming challenge with an unsecure outcome. Response to the treatment is variable and relapses are common. Systemic treatments have multiple systemic side effects and lack of the patient compliance makes intra-lesional therapies not the best choice for treatment of nail psoriasis. We aimed to evaluate and compare the efficacy and side effects of methotrexate versus calcipotriol plus betamethasone two-compound formula when applied topically to psoriatic nails after frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results of our systematic literature review support the role of fractional laser treatment in the management of psoriasis while using topical medications. A total of 7 RCTs have been identified to date, out of which 4 were conducted as intra-patient studies [2,[10][11][12][13][14][15]. Despite the use of different topical medications and varying laser parameters across the studies, all of them have demonstrated a certain degree of reduction in NAPSI (although varying among the different studies).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our systematic literature review support the role of fractional laser treatment in the management of psoriasis while using topical medications. A total of 7 RCTs have been identified to date, out of which 4 were conducted as intra-patient studies [2,[10][11][12][13][14][15]. Despite the use of different topical medications and varying laser parameters across the studies, all of them have demonstrated a certain degree of reduction in NAPSI (although varying among the different studies).…”
Section: Discussionmentioning
confidence: 99%